National Mining Hall of Fame to Induct Six (Society for Mining, Metallurgy & Exploration, 2003)
Six pioneers of the American mining industry will be inducted into the National Mining Hall of Fame on Saturday, Sept. 13, at the Museum Convention Center in Leadville, CO. The 16th annual Mining Hall of Fame induction banquet will begin with a reception and open house at 5:30p.m., followed by the dinner and program at 7 p.m. The six inductees include James M. Gerstley, the only living member, and George O. Argall, Jr.; John F. “Leadville Johnny” Campion; Charles R. Nailler; Edwin N. Pennebaker and Russell L. Wood.